1999
DOI: 10.3758/bf03211947
|View full text |Cite
|
Sign up to set email alerts
|

Object-based visual selective attention and perceptual organization

Abstract: Wereport the results offour experiments that were conducted to examine both the representations that provide candidate entities available for object-based attentional selection and the influence of bottomup factors (i.e., geometric and surface characteristics of objects) and top-down factors (i.e. context and expectancies) on the selection process, Subjects performed the same task in each of the experiments. They were asked to determine whether two target properties, a bent end and an open end of a wrench, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
210
6
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(241 citation statements)
references
References 71 publications
24
210
6
1
Order By: Relevance
“…The present results replicated previous studies demonstrating that object-based attention only selects objects with uniform surface features (Matsukura & Vecera, 2006;Watson & Kramer, 1999). Having replicated this nonuniformity effect, we next asked if the alignment of part structure and surface cues allows object-based attention to select nonuniform objects.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The present results replicated previous studies demonstrating that object-based attention only selects objects with uniform surface features (Matsukura & Vecera, 2006;Watson & Kramer, 1999). Having replicated this nonuniformity effect, we next asked if the alignment of part structure and surface cues allows object-based attention to select nonuniform objects.…”
Section: Resultssupporting
confidence: 77%
“…We next replicated Watson and Kramer's (1999) absence of an object-based effect with multiple-region objects. Observers viewed displays containing two multiple-region objects, each containing two colors that met halfway through the object.…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…Past research has shown that the manifestation of object effects is influenced by a number of factors, including the quality of the object representation and the participants' subjective organization of a stimulus pattern (Avrahami, 1999;Chen, 1998;Watson & Kramer, 1999). For example, response latencies to a target differ as a function of whether the stimulus pattern is perceived as being made of one object or two objects (Chen, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In support of such object-based selection are findings that (1) dividing attention between stimulus elements within the same object is generally more efficient than dividing attention between separate objects (e.g. Duncan 1984;Watson et al 1999;Rodriguez et al 2002) and (2) paying attention to one part of an object results in facilitated processing of stimuli in other parts of the object (Egly et al 1994;Abrams et al 2000;Lamy et al 2002).…”
Section: Introductionmentioning
confidence: 97%